A new class of n-ary hyperoperations. (February 2015) - Leoreanu-Fotea, Violeta; Rosenberg, Ivo; Davvaz, Bijan; Vougiouklis, Thomas
Abstract: To a given n -ary hyperoperation f on a universe H and a unary hyperoperation φ on H we define a new n -ary hyperoperation ∂ f φ on H . We study the associativity, weak associativity and reproductivity of n -ary hyperoperations ∂ f φ .